Território ilustrado: uma investigação da ideia de natureza pelas viagens científicas de Manuel Arruda da Câmara no sertão da Caatinga (1794-1810) - Gomes, Márcia Maria Costa (2021)
At the end of the 18th century and beginning of the 19th, there was an increase in the territorial policy of Portuguese-Brazilian scientific travels in Portuguese America. It aims to investigate the idea of Nature constructed by naturalist Manuel Arruda da Câmara, linked to the territoriality of Portuguese-Brazilian scientific travels in the caatinga sertão in the period from 1794 to 1810. It is about understanding the structure and territorial dynamics of Portuguese-Brazilian scientific travels which involved the social groups of power (political-scientific) in the relationship with the investigation of Nature in the colony, managed by the Portuguese Illustrated metropolis and led by Portuguese-Brazilian naturalists. We opted for the approach of Historical Geography, centered on the study of the past and on the category of territory, based on a methodology of bibliographic and historiographical documentary analysis. The study demonstrated that the Illustrated Territories synthesized not only a spatial configuration of the territorial policy of Luso-Brazilian scientific travels, but an ordering of power and control of Nature by Illustrated science, fostered by Scientific Institutions and Natural History Office Museums . In addition, the research revealed that although Manuel de Arruda da Câmara was intertwined with this structure and dynamics of territorial power of Luso-Brazilian scientific travels, the idea of Nature was guided by two dimensions: by the conflicting interests, of course, that the Caatinga was not the object of study by traveling naturalists or by the Portuguese metropolis; and due to botanical divergences, since Arruda da Câmara classified new species of the caatinga, hitherto unknown in the Linnaean European scientific literature. We observed that the idea of Rudiana Nature was defined by the process of territorialization and its botanical practice embedded in the hinterland of the caatinga, which insisted on scientifically proving to the Portuguese Crown that the caatinga was economically viable. However, there was no rupture of the idea of utilitarian Nature, but of resistance to the Eurocentric theories of degeneration of Nature in Portuguese America.